Coagulation Abnormalities in Lung Cancer: Diagnostic Challenges and Therapeutic Perspectives - Athena Myrou MD, MSc, PhD; Athanasios Penopoulos MD; Konstantinos Barmpagiannos MD; Styliani Ouzouni MD; Fotios Girtovitis MD, PhD (Clinical and Applied Thrombosis/Hemostasis)
Lung cancer is frequently complicated by coagulation abnormalities, primarily presenting as venous thromboembolism (VTE) but also including bleeding events in select patients. This hypercoagulable state arises from a multifaceted interplay between tumor-derived procoagulants, systemic inflammation, endothelial dysfunction, autoimmune mechanisms, and treatment-associated effects. These disruptions not only elevate thrombotic risk but also influence prognosis and therapeutic decisions. Furthermore, the presence of antiphospholipid antibodies or acquired coagulation inhibitors, such as lupus anticoagulant and anti-Factor VIII antibodies, poses a unique clinical challenge by increasing the risk of both thrombosis and hemorrhage. Recent data highlight the expanding role of tumor-derived extracellular vesicles, immune-mediated coagulopathies, and prothrombotic effects of immune checkpoint inhibitors in lung cancer–associated thrombosis. Novel biomarkers-such as prothrombin fragment 1 + 2, integrin β2– positive extracellular vesicles, and endothelial activation markers-are being investigated for risk stratification and personalized treatment decisions. Diagnostic approaches-including coagulation assays, biomarker profiling, and imaging-are discussed alongside emerging tools for individualized anticoagulation and management of acquired inhibitors. Early recognition and tailored management of cancer-associated coagulopathy are essential to improve patient outcomes. This review aims to provide practical insights for clinicians navigating the thrombohemorrhagic spectrum in lung cancer care.